2014
DOI: 10.3390/cancers6010580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuro-Psychological Factors on Smoking-Associated Lung Cancer

Abstract: Smoking has been extensively documented as a risk factor for all histological types of lung cancer and tobacco-specific nitrosamines and polycyclic aromatic hydrocarbons reproducibly cause lung cancer in laboratory rodents. However, the most common lung cancer, non-small cell lung cancer (NSCLC), frequently develops in never smokers and is particularly common in women and African Americans, suggesting that factors unrelated to smoking significantly impact this cancer. Recent experimental investigations in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…No previous neighborhood study has, however, studied both incident and mortality cases of lung cancer. 34 A clinical study has also reported improved survival outcomes with the incidental use of β-blockers among patients with non-small-lung cancer, 35 which suppresses the sympathetic branch of the autonomic nervous system. This study was also unable to do so, although we adjusted for COPD, tobacco abuse, and alcoholism, in an attempt to adjust for potential surrogates for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…No previous neighborhood study has, however, studied both incident and mortality cases of lung cancer. 34 A clinical study has also reported improved survival outcomes with the incidental use of β-blockers among patients with non-small-lung cancer, 35 which suppresses the sympathetic branch of the autonomic nervous system. This study was also unable to do so, although we adjusted for COPD, tobacco abuse, and alcoholism, in an attempt to adjust for potential surrogates for smoking.…”
Section: Discussionmentioning
confidence: 99%
“… 2012 ; Schuller 2012 ; Chu et al. 2013 ; Warren & Singh 2013 ; Grando 2014 ; Niu & Lu 2014 ; Schaal & Chellappan 2014 ; Schuller 2014 ). For example, nicotine has been reported to stimulate cell proliferation, inhibit apoptosis, induce cell migration and invasion, induce angiogenesis and inhibit immune functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, chronic stress was found to promote tumor growth in immunodeficient nude mice carrying defects in immune functions (6,9,(33)(34)(35). Hence, additional mechanisms, such as somatic mutations, genomic instability, and inhibited apoptosis, have been proposed to explain the effects of chronic stress on tumor development (5,35). Our study provides direct evidence that the norepinephrineinduced activation of IGF-1R in lung epithelial cells is a biochemical event that promotes lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 62%
“…Chronic stress has been implicated in the onset and progression of various cancers, including lung cancer (6,9,13,(33)(34)(35). Lung cancer patients with severe psychologic distress at the time of diagnosis had frequently experienced earlier psychologic stress (36), and psychologic distress was found to be a significant predictor of lung cancer mortality (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation